Evolving role of North African civil society actors in the foreign policymaking process: youth, women's, labour and human rights organisations. Issue 4 (4th July 2019) - Lynn Dobbs, Kirstie; Schraeder, Peter J.
ABSTRACT: This article examines the evolving foreign policy roles of four sets of civil society actors – youth, women's, labour and human rights groups – in Algeria, Egypt, Libya, Morocco and Tunisia during the Arab Spring and beyond. Our findings demonstrate that civil society groups initially flourished in the Arab Spring, with the region's average 'civil society rights score' registering positive increases in 2011 and 2012. The period of 2013 to 2018 witnessed a deterioration in this average score, as civil society faced an authoritarian backlash from illiberal (authoritarian) and liberal (democratic) North African regimes. An examination of individual civil society organisations further demonstrates a range of influence on foreign policy. Youth groups exert the least impact on North African foreign policies, despite high expectations associated with their central role in revolutionary protests and change associated with the Arab Spring. In contrast, women's, labour and especially human rights organisations have played more influential if still limited foreign policy roles. Finally, the impact of civil society on foreign policy is strongly mediated by a country's level of democracy. Only in Tunisia, which made a successful transition to democracy, have civil society organisations in the post-Arab Spring continuously enjoyed the freedoms to organise, protest and provide input into policy, including foreign policy.